3D printing – Present and future – A Chemical Engineering perspective - Amores, Isabel Diañez; González-Gutiérrez, Joamin; García, I. Martínez; Franco, José M.; Gallegos, Críspulo (Chemical engineering research & design, 2022)
3D printing (3DP) has emerged in recent years as a form of processing with many exciting aspects. Today, it finds use in the industrial sector as well as among private individuals and small manufacturers, bringing manufacturing closer to end users and helping to bring a multitude of ideas and innovations to life. In this scenario, Chemical Engineering could play an essential role in 3DP, while it can also receive and benefit from many of the characteristics of this technology. This paper aims to highlight those that we consider the most productive meeting points between Chemical Engineering and 3DP, as well as the new techniques and applications that could benefit from this tandem in the future. [Display omitted] •3DP processes can benefit from knowledge available in many Chemical Engineering topic areas.•The creation of unique and/or complex-shaped objects by 3DP can be of great interest to Chemical Engineering.•The relationship between Chemical Engineering and 3DP is not evident to many chemical engineers.•Including 3DP in the curriculum can enhance students’ learning motivation towards different engineering subjects.